Fire and vegetation: Introduction to the special issue - Silveira, Fernando A.O.; Rossatto, Davi R. [UNESP]; Heilmeier, Hermann; Overbeck, Gerhard E (Elsevier, 2022)
Fires are widespread disturbance events with many implications for different aspects of plant persistence and vegetation properties. Changing fire regimes can profoundly affect vegetation dynamics and ecosystem properties. Recent steep increases in the frequency of fires worldwide and the occurrence of megafires have caught the attention of scientists, policymakers, and the media. The FLORA Special Issue on Fire and Vegetation unites five invited Opinion Papers with emphasis on South America and nineteen research papers, including one review, on different aspects of the fire–vegetation interaction. The studies contribute both to the discussion of how to better manage fire in ecosystems and to improve our understanding of fire effects on organisms, communities, and ecosystems. Our expectation is that the Special Issue stimulates further research and, ultimately, helps to inform fire management practice to improve human well-being, to ensure the sustainability of resource use, and perhaps most important, biodiversity conservation and climate change mitigation.
Keywords: Cerrado; Fire management; Grassland; Pantanal; Plant functional traits; Plant morpho-physiology; Plant regeneration; Species composition